2012
DOI: 10.4110/in.2012.12.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 1E8 Single Chain Fv-Fc Construct Against Human CD59

Abstract: BackgroundTherapeutic approaches using monoclonal antibodies (mAbs) against complement regulatory proteins (CRPs:i.e.,CD46,CD55 and CD59) have been reported for adjuvant cancer therapy. In this study, we generated a recombinant 1E8 single-chain anti-CD59 antibody (scFv-Fc) and tested anti-cancer effect.by using complement dependent cytotoxicity (CDC).MethodsWe isolated mRNA from 1E8 hybridoma cells and amplified the variable regions of the heavy chain (VH) and light chain (VL) genes using reverse-transcriptase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Currently, anti-C5aR1 in combination with anti-PD-1/PD-L1 is being studied in clinical trials for the treatment of patients with advanced solid tumors (NCT03665129). Adjuvant cancer therapy is utilizing monoclonal antibodies (mAbs) directed against complement regulatory proteins (CRPs), including CD46, CD55, and CD59 [ 115 ]. Sherbenou and colleagues reported that CD46 antibodies kill tumor cells by apoptosis while protecting benign cells [ 116 ].…”
Section: Therapeutic Potential Of Modulating Complement System In Liv...mentioning
confidence: 99%
“…Currently, anti-C5aR1 in combination with anti-PD-1/PD-L1 is being studied in clinical trials for the treatment of patients with advanced solid tumors (NCT03665129). Adjuvant cancer therapy is utilizing monoclonal antibodies (mAbs) directed against complement regulatory proteins (CRPs), including CD46, CD55, and CD59 [ 115 ]. Sherbenou and colleagues reported that CD46 antibodies kill tumor cells by apoptosis while protecting benign cells [ 116 ].…”
Section: Therapeutic Potential Of Modulating Complement System In Liv...mentioning
confidence: 99%